CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. FINNANTARA INTIGA MELALUI PROGRAM DESA MAKMUR PEDULI API (DMPA) BIDANG PERTANIAN PANGAN - Ricca Gideon; Eva Dolorosa; Josua Parulian Hutajulu (JSEP (Journal of Social and Agricultural Economics), 2021)
The Desa Makmur Peduli Api (DMPA) Program is a form of Corporate Social Responsibility (CSR) from PT. Finnantara Intiga. This program aims to empower the local community in a productive economic sector which focuses on increasing the local people's income. The various DMPA programs that have been prepared are fish farming, cattle farming, rice, and corn farming. Based on the results of the study and agreement with the local community, the DMPA program focuses on corn farming. The purpose of this study was to determine a strategy to improve the performance of corn farming. The research method uses descriptive methods with SWOT analysis tools to determine strategic alternatives and QSPM analysis to select strategic priorities. The respondents consisted of 4 key informants and 18 regular informants for SWOT analysis and 4 experts for QSPM analysis. The result of the SWOT analysis is WO (Weakness - Opportunity) strategy with 4 alternative strategies. Based on the results of the QSPM analysis, the priority strategy is for the company have to collaborate with the government to train farmers routinely.